PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP RISIKO KREDIT PERUSAHAAN PERBANKAN (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2012 - 2016) - Rizki Yogonugroho, Muhammad; Muharam, Harjum (Diponegoro Journal of Management, 2018)
The problem of this research is that there is a trend of an increase in credit risk in 2012 to 2016. This condition is a phenomenon because national banks are able to disburse credit to many developing companies, but the phenomenon of increasing NPLs shows that banks have increasing credit risk. This is also supported by the gap research, namely the inconsistent results of research on credit risks that are different. This study aims to analyze the effect of the size of the board of directors, the size of the board of commissioners, the concentration of share ownership, managerial share ownership and management compensation on the credit risk of Banking Companies Registered on the IDX 2012-2016.The sample used in this study were Banking Companies Registered on the Stock Exchange in 2012 - 2016. The sampling technique used was purposive sampling. Data collection methods in this study use documentation. Data analysis method uses multiple linear regression analysis.Based on the results of the study, managerial ownership has a negative effect on credit risk, the concentration of share ownership has a positive effect on credit risk while the size of the board of directors, the size of the board of commissioners, and management compensation does not affect credit risk..